The Urgency Of The Mobile Sharia Service Program at BPD Kaltimtara Syariah as Supporting IKN Development - hasbi, muhammad (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
The market opportunity for sharia banks is still very large, which is a challenge for sharia banks to attract and convert Muslim people into customers. Kutai Kartanegara Regency is one of the districts of East Kalimantan province which has an area of 27,263.10 km² and has a large potential market for sharia customers. This type of research is called field research, and the research approach in this research is a descriptive qualitative approach. This research was carried out at Bank Kaltim Syariah Tenggarong branch and other that have implemented the Sharia Mobile Service program as well as customers who use and do not use sharia product services in several border sub-districts in Kutai Kartanegara district. Data collection techniques through observation, interviews and documentation as well as data analysis techniques through qualitative descriptive analysis in this research, namely, explaining the urgency of community needs-based sharia mobile services. The sharia mobile service program already exists at the Kaltimtara Bank Balikpapan and Samarinda branches, but website do not match those carried out in the field. Bank Kaltimtara Syariah North Penajam Paser sub-branch and Tenggarong Kutai Kartanegara Branch need to have sharia mobile service vehicles for both of them. This has been reviewed from 5 conditions, namely the economic condition of the community, socio-cultural demographics/psychography of the community, politics , government, and law, technology, and competitive factors. The results went to the people of Kutai Kartanegara Regency,the community wants sharia-based services and takes into account the pick-up and drop-off services available in the Sharia Mobile Service program as well as financing that is profitable for customers.